2006
DOI: 10.1007/s11092-006-9018-z
|View full text |Cite
|
Sign up to set email alerts
|

Building Instructional Leaders’ Capacity to Deliver Constructive Feedback to Teachers

Abstract: The aim of this action research study was to enhance the instructional leadership capacity of aspiring school leaders, through a practical learning experience. The participants observed classes, collected classroom-based data, prepared and delivered written constructive feedback to teachers. Findings suggest that aspiring school leaders need to develop a knowledge foundation related to quality instruction, teachers respond in a positive way and appreciate the feedback offered, constructive feedback has potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 8 publications
0
30
0
9
Order By: Relevance
“…Articles from behaviourism (e.g., Auld et al, 2010;Goodman et al, 2008), cognitivism (e.g., Shute, 2008), social cultural theory (Ackan & Tatar, 2010;Brinko, 1993;Yeh & Lo, 2009) and social constructivism (Colasante, 2011;Gielen et al, 2010) indicated that feedback should be specific and clear. Others used different terms: feedback should be concrete (Brinko, 1993) consistent (Brinko, 1993;Ovando, 2005; from social cultural theory), and descriptive (Fund, 2010;Kretlow & Bartholomew, 2010; from social constructivism).…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Articles from behaviourism (e.g., Auld et al, 2010;Goodman et al, 2008), cognitivism (e.g., Shute, 2008), social cultural theory (Ackan & Tatar, 2010;Brinko, 1993;Yeh & Lo, 2009) and social constructivism (Colasante, 2011;Gielen et al, 2010) indicated that feedback should be specific and clear. Others used different terms: feedback should be concrete (Brinko, 1993) consistent (Brinko, 1993;Ovando, 2005; from social cultural theory), and descriptive (Fund, 2010;Kretlow & Bartholomew, 2010; from social constructivism).…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
“…Furthermore, these learning theories both suggested that feedback should be accurate and irrefutable (Brinko, 1993;Gielen et al, 2010) and feedback should be relevant and meaningful (Ackan & Tatar, 2010;Brinko, 1993;Martens et al, 2010;Ovando, 2005).…”
Section: Feedback Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okul yöneticilerinin, öğrencilerin daha iyi öğrenmesi amacıyla öğretimsel yönetim bağlamında üstlenmesi gereken bazı roller ve sorumluluklar bulunmaktadır. Bu roller ve sorumluluklar; okuldaki öğretmenlerle işbirliği yapmak, sınıfları ve öğrencileri gözlemlemek, öğretmenlere öğretimsel materyallere ulaşma konusunda yardımcı olmak (Lynch, 2012); güven ve huzur dolu bir çalışma ortamı oluşturmak (O'Donnell ve White, 2005); öğrenci başarısıyla ilgili verileri analiz etmek (Neumerski, 2013); takım çalışması ve sorumlulukları paylaşmak (Gümüş ve Akçaoğlu, 2013); sistematik olarak sınıfa dayalı veriler toplamak ve öğretmenlerden yazılı geribildirimler almak (Ovando, 2005); gerektiğinde öğretmenlerle konuşmak ve mesleki gelişimleri konusunda onlara yardımcı olmaktır (Blasé ve Blasé, 2000). Bütün bu uygulamalar okul yöneticilerinin "öğrenme lideri" olmasını gerektirmektedir (Pont, Nusche ve Moorman, 2008).…”
Section: Tartışma Ve Sonuçunclassified
“…Dünya genelinde yaygınlaşmaya başlayan hesap verebilirlik yaklaşımları, eğitimin niteliğini artırmaya yönelik standartlar ve beklentiler ve okul geliştirme yaklaşımları eğitimcilere, okul yöneticilerine ve öğretmenlere yeni roller ve sorumluluklar yüklemiştir (Firestone ve Riehl, 2005;Ovando, 2005;Stronge, Richard ve Catano, 2008). Bu roller ve sorumlulukların merkezinde okul yöneticileri yer almaktadır.…”
Section: Introductionunclassified